Location Tracking Using Bluetooth iTag - Joseph Dedy Irawan; Yudi Limpraptono; Emmalia Adriantantri (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2020)
Bluetooth iTag is an electronic technology development, particularly in the field of data communication between devices. In this study, a keychain that can communicate with other devices uses Bluetooth communication for location tracking and searching for lost items. Developing an application to determine this location starts with the connection to a Bluetooth device and continues by determining the location of the Bluetooth iTag. After tracking the location, this application can be further developed as several other applications, such as searching for lost items, monitoring the locations of young children and pets and other applications.DOI : https://doi.org/10.26905/jeemecs.v3i2.4017